Exploring the promise of virtual reality in enhancing anatomy education: a focus group study with medical students - Abundez Toledo, Maximiliano; Ghanem, Ghadi; Fine, Stuart; Weisman, Daniel; Huang, Yue Ming; Rouhani, Amir A. (Frontiers in Virtual Reality, 2024)
Virtual reality (VR) has the potential to be used as a transformative tool in medical education -offering both interactive models and clinical simulations to enhance training. VR presents a space and cost-effective solution for remote education, combined with prospects of higher efficiency and interactivity than traditional training. This study aimed to explore the potential application and perception of VR in a focus group of medical students as an innovative tool for learning anatomy. Sixteen students underwent a structured VR lesson plan exploring concepts in anatomy. Pre-and post-surveys assessed participants' exposure to VR, previous exposure to and preparedness in anatomy training, and attitudes toward VR. Results revealed that despite limited prior exposure to VR, participants found the technology both easy to navigate and comfortable to use. Notably, over 90% of students indicated that VR would enhance their anatomy learning experience and help them learn a topic better than traditional models. Furthermore, 94% of participants agreed that this learning modality should be offered to medical students, and if given access to this technology, most would utilize it for learning anatomy and potentially for other subjects as well. This study emphasizes VR's potential to enhance medical education, particularly in anatomy instruction. VR's adaptability, user-friendly interface, and positive student perceptions highlight its viability as a supplemental tool. Future research should explore specific anatomy applications, long-term impacts on knowledge retention, and the evolving role of VR in medical education.